Growing Up with Asperger’s Syndrome: Developmental Trajectory of Autobiographical Memory - Bon, Laetitia; Baleyte, Jean-Marc; Piolino, Pascale; Desgranges, Béatrice; Eustache, Francis; Guillery-Girard, Bérengère (Frontiers in Psychology, 2013)
Autobiographical memory and social cognition share common properties and both are affected in autism spectrum disorders (ASD). So far, most of the scant research in ASD has concerned adults, systematically reporting impairment of the episodic component. The only study to be conducted with children concluded that they have poorer personal semantic knowledge than typical developing children. The present study explores the development of both components of autobiographical memory in an 8-year-old boy diagnosed with Asperger’s syndrome, based on three examinations in 2007, 2008 and 2010. On each occasion, he underwent a general neuropsychological assessment including theory of mind tasks, and a specially-designed autobiographical memory task allowing us to test both the semantic and the episodic components for three lifetime periods (current year, previous year and earlier years). We observed difficulties in strategic retrieval and theory of mind, with a significant improvement between the second and third examinations. Regarding autobiographical memory, different patterns of performance were noted in all three examinations: 1) relative preservation of current-year personal knowledge, but impairment for the previous and earlier years, and 2) impairment of episodic memory for the current and previous year, but performances similar to those of controls for the earlier years. The first pattern can be explained by abnormal forgetting and by the semanticization mechanism, which needs verbal communication and social interaction to be efficient. The second pattern suggests that the development of episodic memory only reached the stage of “event memory”. This term refers to memory for personal events lacking in details or spatiotemporal specificity, and is usually observed in children younger than 5. We conclude that the abnormal functioning of social cognition in ASD, encompassing social and personal points of view, has an impact on both components of autobiographical memory.